Early life factors are associated with trajectories of consistent organized sport participation over childhood and adolescence: Longitudinal analysis from the Raine Study. Issue 4 (April 2019) - Howie, Erin K.; Ng, Leo; Beales, Darren; McVeigh, Joanne A.; Straker, Leon M.
Abstract: Objectives: The purpose of this study was to identify early life factors that were associated with childhood and adolescent organized sport participation trajectories. Design: Participants were in the Raine Study, a pregnancy cohort in Western Australia recruited from 1989 to 1991. Methods: Three organized sport trajectories over ages 5–17 years were previously identified for girls (n = 824: consistent participators, dropouts, and non-participators in sport) and boys (n = 855: consistent participators, dropouts, joiners — those who joined sport in adolescence). Physical, psychological and social factors were measured from birth to age 5. Results: For girls and boys, children who were breastfed, were taller, did not have behavior problems, and attended childcare were more likely to consistently participate. Girls who had a previous injury (Relative risk ratio 1.55: 95% confidence interval 1.05, 2.29 vs never been injured) or who had parents who had worries about their child's health (1.56: 1.00, 2.42 vs no worries) were more likely to be in the dropout trajectory. Boys born preterm (2.00, 2.06, 3.76 vs full-term), did not have a previous injury (0.72, 0.53, 0.97 those with injury vs never been injured), had more difficult temperament (1.63, 1.02, 2.60 vs easy temperament), and higher family dysfunction (1.49, 1.06, 2.08) were more likely to be in the dropout trajectory. Conclusions: Early life factors were associated with membership in sport trajectories. Physical, psychological, and social factors may serve as early warning signs for parents and practitioners that children may be at higher risk of dropping out of sports.